Wetland Restoration Shanghai Dalian Lake Project - An, Shuqing; Wang, Limin (Springer Environmental Science and Engineering, 2014)
Wetland Restoration: Shanghai Dalian Lake Project introduces the whole Shanghai Dalian wetland restoration process, including the background investigation of the wetland, the master planning of wetland restoration, more detailed design, engineering construction and engineering effect assessment. This book appeals to readers especially due to its detailed data on wetland restoration. Readers can carry out a similar project step by step from the initial investigation to the last assessment by following the structure presented in this work. Through this book, we can get first-hand information on a wetland restoration, but it can also be valuable for other projects investigators. Professor Shuqing An works at Nanjing University, China. Dr. Limin Wang works at World Wild Fund for Nature, China.